Sistem Kontrol LED IoT Menggunakan Wi-Fi melalui Bot Telegram - Mutiarani, Mutiarani; Ritonga, Rizki Ramadani (Journal of Computer Science and Informatics Engineering, 2025)
This study develops an IoT-based LED control system operated through the Telegram application, using Wi-Fi connectivity. The system is designed to allow users to remotely control the LED lighting, including turning it on, off, or adjusting its intensity, using a Telegram bot as the control interface. A microcontroller connected to a Wi-Fi module receives commands from the Telegram bot via a server and executes the instructions to control the LED. Optimization was conducted to ensure energy efficiency and improve the system’s response time to user commands. Testing demonstrated that the system performs responsively and stably under various network conditions, with low power consumption. This approach provides an efficient and user-friendly solution for LED IoT control systems, suitable for smart home applications or industrial environments requiring remote lighting control via Telegram.